KELAYAKAN POSTER KANDUNGAN GIZI ANGGUR PADA SUB MATERI ZAT MAKANAN KELAS XI SMA - Kurniati, Sri; Daningsih, Entin; ., Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
This study aimed to know the feasibility of poster about grape (Vitis vinifera L.) nutrient content which were sold in Pontianak as a learning medium on sub material of nutrient in class XI SMA. This study was descriptive with questionnaire as non-test data technique collection. Validation was done by the experts; they were 2 Biology Education lectures and 3 biology high school teachers in Pontianak. The technique of data analysis used Content Validity Ratio (CVR) and Content Validity Index (CVI). The result of data analysis showed that the poster was feasible for a medium learning for the material sub class XI SMA nutrients the entire assessment criteria had reached the minimum Lawshe CVR value that was equal to 0.99. Keywords: poster feasibility, grape nutrient, fiber